Mesothelioma Risk Among Maritime Workers According to Job Title: Data From the Italian Mesothelioma Register (ReNaM) - Vimercati, Luigi; Cavone, Domenica; Negrisolo, Omero; Pentimone, Floriana; De Maria, Luigi; Caputi, Antonio; Sponselli, Stefania; Delvecchio, Giuseppe; Cafaro, Francesco; Chellini, Elisabetta; Binazzi, Alessandra; Di Marzio, Davide; et al. (La Medicina del Lavoro, 2023)
The study describes the 466 cases of malignant mesotheliomas (MM) collected by the National Mesothelioma Register (ReNaM) in Italy in the period 1993-2018 relating to subjects with exclusive asbestos exposure in merchant or military navy. The cases among maritime workers represent 1.8% of the total cases with defined exposure registred in the ReNaM, of which 212 cases (45.4%) among merchant maritime workers and 254 cases (54.5%) among navy. The distribution by site of mesothelioma showed 453 (97.2%) MM cases of the pleura, 11 (2.3%) of the peritoneum and 2 (0.4%) of the tunica vaginalis of the testis. With regard to occupational exposure, it was classified as certain in 318 (68.2%) cases, probable in 69 (14.8%) cases and possible in 79 (16.9%) cases. Among the 23 classified jobs, the highest percentages of certain exposures are among naval engineers, motor mechanics, machine captains and sailors. Machine crew accounted for 49.3% of the cases, deck crew for 27.6%. All cases began exposure on board between 1926 and 1988. Seamen were exposed to asbestos while at sea by virtue of living onboard ships and from continual release of asbestos fibers due to the motion of a vessel. Epidemiological surveillance through the ReNaM has allowed us to verify among cases in the maritime, navy and merchant marine sectors, that in the past, subjects were exposed regardless of the ship's department where have provided service therefore all these cases must be considered as occupational diseases.